2015
DOI: 10.1002/jor.23009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated marrow inflammatory cells and osteoclasts in subchondral osteosclerosis in human knee osteoarthritis

Abstract: Subchondral osteosclerosis, characterized by an increase of hypomineralized bone material, is a pathological hallmark of osteoarthritis. The cellular components in the subchondral marrow compartment that participate in this aberrant bone remodeling process remain to be elucidated. This study assessed the presence of marrow inflammatory cells and their relative abundance between nonsclerotic and sclerotic tissues in knee osteoarthritis. Bone samples from osteoarthritic knee tibial plateaus were stratified for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 41 publications
(64 reference statements)
2
40
0
2
Order By: Relevance
“…These data are in line with studies by Krause et al [3] and Yonetani et al [26] who also showed viable subchondral trabeculae in juvenile OCD lesions arthroscopically classified according to the International Cartilage Repair Society (ICRS) OCD as ICRS OCD I/II [27]. A recent paper described a greater presence of TRAP-positive cells in sclerotic bone than in nonsclerotic bone areas, which is a typical feature in advanced OA [28], suggesting that the presence of TRAP-positive cells in bone focal lesion may contribute to a sclerotic bone evolution.…”
Section: Discussionsupporting
confidence: 87%
“…These data are in line with studies by Krause et al [3] and Yonetani et al [26] who also showed viable subchondral trabeculae in juvenile OCD lesions arthroscopically classified according to the International Cartilage Repair Society (ICRS) OCD as ICRS OCD I/II [27]. A recent paper described a greater presence of TRAP-positive cells in sclerotic bone than in nonsclerotic bone areas, which is a typical feature in advanced OA [28], suggesting that the presence of TRAP-positive cells in bone focal lesion may contribute to a sclerotic bone evolution.…”
Section: Discussionsupporting
confidence: 87%
“…Kim et al have also demonstrated increased CD11d‐positive cell (monocyte/macrophage) infiltration and cytokine production in capsular tissues from severely degenerated facet joints. In a previous study, we have demonstrated enhanced marrow macrophage infiltration in subchondral bone sclerosis in knee osteoarthritis . The precise pathological role of enhanced macrophage abundance needs to be established, but recent studies revealed that these cells regulate bone remodelling in health and disease …”
Section: Discussionmentioning
confidence: 92%
“…In a previous study, we have demonstrated enhanced marrow macrophage infiltration in subchondral bone sclerosis in knee osteoarthritis. 15 The precise pathological role of enhanced macrophage abundance needs to be established, but recent studies revealed that these cells regulate bone remodelling in health and disease. 34 Subchondral bone histopathology of facet joint osteoarthritis in lumbar spinal stenosis is characterized by marrow infiltration by macrophage-rich tissues and enhanced de novo bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations